Thermal shock behaviour of H and H/He-exposed tungsten at high temperature. (18th January 2016) - Lemahieu, N; Greuner, H; Linke, J; Maier, H; Pintsuk, G; Wirtz, M; Oost, G Van; Noterdaeme, J-M
Abstract: Polycrystalline tungsten samples were characterized and exposed to a pure H beam or mixed H/He beam containing 6% He in GLADIS at a surface temperature of 600 °C, 1000 °C, or 1500 °C. After 5400 s of exposure time with a heat flux of 10.5 MW m −2, the total accumulated fluence of 2 × 10 25 m −2 was reached. Thereafter, edge localized mode (ELM)-like thermal shocks with a duration of 1 ms and an absorbed power density of 190 MW m −2 and 380 MW m −2 were applied on the samples in JUDITH 1. During the thermal shocks, the base temperature was kept at 1000 °C. The ELM-experiments with the lowest transient power density did not result in any detected damage. The other tests showed the beginning of crack formation for every sample, except the sample pre-exposed with the pure H-beam at 1500 °C in GLADIS. This sample was roughened, but did not show any crack initiation. With exception to the roughened sample, the category of ELM-induced damage for the pre-exposed samples is identical to the reference tests without pre-exposure to a particle flux.